2014
DOI: 10.1108/lht-12-2013-0157
|View full text |Cite
|
Sign up to set email alerts
|

Open Source Software solutions in Indian libraries

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…The presence of FOSS in the digital library (DL) software category, i.e., DSpace, Eprint, and GSDL, and in ILMS category, Koha and Newgenlib, was examined by Hanumappa (2014).…”
Section: The Concept Of a Digital Librarymentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of FOSS in the digital library (DL) software category, i.e., DSpace, Eprint, and GSDL, and in ILMS category, Koha and Newgenlib, was examined by Hanumappa (2014).…”
Section: The Concept Of a Digital Librarymentioning
confidence: 99%
“…The presence of FOSS in the digital library (DL) software category, that is, DSpace, Eprint and GSDL, and in ILMS category, Koha and Newgenlib, was examined by Hanumappa et al (2014). The migration or adoption of FOSS among Indian libraries has drawn considerable interest from institutions recently, as the benefits to the library become better known.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Software comparison and assessment studies (e.g. Krishnamurthy, 2008;Hanumappa et al, 2014) overview general software functions and available software packages, and may review the organizations and development communities behind them. Other comparison studies (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are 19 open source ILS available (Foss4lib, 2018), and amongst the available open source ILSs, Koha, Evergreen and OPAL have emerged as the widely adopted and popular open source ILS (Breeding, 2009). Hanumappa et al (2014) in their study explored OSS relevant to Indian libraries and found that Koha and NewGenLib were most preferred open source ILS in Indian libraries. Of late, several researches were carried out primarily examining the outcome of adoption of open source ILS.…”
Section: Literature Reviewmentioning
confidence: 99%